Treatment for Mycobacterium abscessus complex–lung disease - Weng, Ya-Wei; Huang, Chun-Kai; Sy, Cheng-Len; Wu, Kuan-Sheng; Tsai, Hung-Chin; Lee, Susan Shin-Jung (Journal of the Formosan Medical Association, 2020)
Nontuberculous mycobacterial infections and colonization are becoming more prevalent worldwide. Mycobacterium abscessus complex (MABC) is one of the predominant pathogens capable of a wide spectrum of infections, with 50% of infections involving the lungs. The decision to commence treatment is determined according to the severity of the disease, risk of progressive disease, presence of comorbidities, and goals of treatment. MABC is resistant to standard antituberculous agents and has variable drug susceptibility across different geographical locations, therefore, antibiotic susceptibility testing of all clinically significant isolates is crucial for selecting a treatment strategy. Pulmonary infections due to MABC is difficult to cure using the currently recommended regimens from the American Thoracic Society and British Thoracic Society. Macrolides are the cornerstone of treatment, but the efficacy of macrolide-based chemotherapy may be compromised by resistance. Despite the introduction of new drugs for treatment, treatment outcomes remain unsatisfactory. The combination of surgical resection of limited lung disease regions with a multidrug, macrolide-based therapy offers the optimal chance of achieving clinical cure of the disease. This review focuses on medical treatment of MABC–lung disease and the efficacy of new agents, such as clofazimine, amikacin inhalation therapy, tigecycline and linezolid, for treating MABC–lung disease.